An energy landscape for carbon network solids - Powles, R.; Marks, Nigel; Lau, D.; McCulloch, D.; McKenzie, D. (Pergamon, 2013)
Carbon network solids show a rich diversity with many distinct structural classes. Transitions between classes can be induced by annealing and mechanical compression, frequently with unexpected results. We have constructed an energy landscape based on atomistic simulations that includes both amorphous and crystalline bonded networks. The landscape, representing a minimum free energy surface, is constructed as a function of density and the degree of crystallinity and is used to explain experimental observations. We use the landscape to explain: (1) why some carbon structures show full recovery from deformation while others deform permanently, (2) why annealing of non-crystalline materials grown in a low pressure pure carbon vapor quenching process always lead ultimately to graphite and not to diamond and (3) why room temperature compression of graphitic carbons leads to a reversible amorphization. The tetrahedrally bonded amorphous structure is predicted to have the lowest free energy at sufficiently high pressures and temperatures and therefore is expected to occur as the endpoint of rapidly quenched shock compression processes of carbon structures.